Dietitians can improve accuracy of prescribing by interacting with electronic prescribing systems - Simon Ball; Susan De Waal; Laurie Lucas; Tanya Pankhurst (BMJ Health & Care Informatics)
Background Dietitians increasingly interact with electronic health records (EHRs) and use them to alert prescribers to medication inaccuracies.Objective To understand renal dietitians’ use of electronic prescribing systems and influence on medication accuracy in inpatients. In outpatients to determine whether renal dietitians’ use of the electronic medication recording might improve accuracy.Methods In inpatients we studied the impact of dietetic advice on medical prescribing before and after moving from paper recommendations to ePrescribing. In outpatients, when dietitians recommended changes in dialysis units, we assessed the time to patients receiving the new medications. We trained dietitians to use the ePrescribing system and assessed accuracy of medication lists at the start and end of the study period.Results Inpatients: before the use of EHRs, 25% of proposals were carried out and took an average of 20 days. This rose to 38% using an EHR and took an average of 4 days.Outpatients: in dialysis units dietitians recommend initiating and stopping medications and advise on repeat medications. Most recommendations were during multidisciplinary team (MDT) meetings; the average time to receive medications was 10 days. Drug histories updated by dietitians increased after the start of the study and accuracy of medication lists improved from 2.4 discrepancies/patient to 0.4.Conclusion Dietitians can make medication suggestions directly using EHR, delivering more timely change to patient care and improving accuracy of patients’ medication lists. Allowing the whole of the MDT to contribute to the EHR improves data completeness and therefore patient care is likely to be enhanced.